(untitled) (Current Horticulture, 2024)
The experiment was conducted to assess variation among existing guava (Psidium guajava L.) trees of seedling origin. A total of 60 healthy and bearing trees were marked for studies during 2017-18 at RHR&TS, Dhaulakuan, Himachal Pradesh. There was variation in fruit shape (round to pyriform), colour of fruit skin (yellow, yellow white and yellow green) and fruit shape at stalk end (rounded to broadly rounded). The variation in fruit weight, fruit length, fruit width, length/width ratio, number of seeds/ fruit, fruit yield, yield efficiency, TSS, acidity, ascorbic acid, total sugars, reducing sugars, non-reducing sugars were 65.22-128.57g, 4.40-6.18, 4.90-6.51, 0.87-1.31cm, 12-411, 16.0-34.8kg/tree, 2.27-24.6g/cm2, 7.35-11.83oBrix, 0.270-0.627%, 138.19-249.43mg/100g, 5.13-8.38%, 3.22-5.44% and 1.81-2.83%, respectively. Out of 60 trees, four were designated as “elite” based on overall distinct attributes. The identification of one seedless (tree No. 22), one approximate seedless (tree No. 21), two red fleshed genotypes (tree No. 57 and tree No. 58) having desirable horticulture traits was a significant finding.